Understanding Sustainability: The Importance of Sustainable Development and Comprehensive Planning - Jeffrey P. Gellermann; Mark A. Brennan; Devesh Nirmul; Karla Lenfesty (EDIS)
FCS-7237, a 6-page paper by J.P. Gellerman, M.A. Brennan, Devesh Nirmul, and Karla Lenfesty, discusses sustainable development — different perspectives, aspects of sustainable communities, and strategies for achieving sustainable communities. Includes references. Published by the UF Department of Family Youth and Community Sciences, September 2009.